EFEKTIVITAS PENGGUNAAN LEGIN DAN MULSA JERAMI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI HITAM (Glycine soya Benth ) - Eko Supriyanto; Tri Rahayu; Sri Juli Rachmawatie (Jurnal Agroekoteknologi, 2021)
This research was conducted to determine the effectiveness of  legin and straw mulch treatment on the growth and yield of black soybean plants. This research was conducted from June 2020 to September 2020, at Ngablak, Kemuning, Ngargoyoso, Karanganyar Regency with an altitude of 750 m above the sea. This study used a factorial method with randomized complete block design (RCBD) consisting of two factors. The first  factor is giving straw mulch E (E0 = without pulsing, E1 = with straw mulch). The second  factor is the various doses of legin H (H0 = without legin, H1 = 7,5 kg / g seeds, H2 = 15 g / kg seeds, H3 = 22,5 g / kg seeds). The data obtained were analized using analysis of variance followed by Duncan's multiple Range test (DMRT) at the 5% level. The results showed that the treatment of straw mulch (E) had a very significant effect on all parameter observed. The treatment of various doses of legin and the interaction between mulching and legin were not significantly effect  for the five parameters observed .Combination of E1H2 treatment (with straw and legin mulch at a dose of 15 g / kg of seed)had highest yield weight of dry biomassa per plant 36.42 g, weight of dry seed per plant 27.84 g and weight of dry seeds per plot 479.12 g. The treatment of E0H0 (without straw mulch and without legin) had the lowest yield to all parameter observed.